CRISPR-based bioengineering in microalgae for production of industrially important biomolecules - Dhokane, Dhananjay; Shaikh, Arshi; Yadav, Anu; Giri, Nandinee; Bandyopadhyay, Anindya; Dasgupta, Santanu; Bhadra, Bhaskar (Frontiers in Bioengineering and Biotechnology, 2023)
Microalgae, as photosynthetic organisms, have the potential to produce biomolecules for use in food, feed, cosmetics, nutraceuticals, fuel, and other applications. Faster growth rates and higher protein and lipid content make microalgae a popular chassis for many industrial applications. However, challenges such as low productivity and high production costs have limited their commercialization. To overcome these challenges, bioengineering approaches such as genetic engineering, metabolic engineering, and synthetic biology have been employed to improve the productivity and quality of microalgae-based products. Genetic engineering employing genome editing tools like CRISPR/Cas allows precise and targeted genetic modifications. CRISPR/Cas systems are presently used to modify the genetic makeup of microalgae for enhanced production of specific biomolecules. However, these tools are yet to be explored explicitly in microalgae owing to some limitations. Despite the progress made in CRISPR-based bioengineering approaches, there is still a need for further research to optimize the production of microalgae-based products. This includes improving the efficiency of genome editing tools, understanding the regulatory mechanisms of microalgal metabolism, and optimizing growth conditions and cultivation strategies. Additionally, addressing the ethical, social, and environmental concerns associated with genetic modification of microalgae is crucial for the responsible development and commercialization of microalgae-based products. This review summarizes the advancements of CRISPR-based bioengineering in microalgaefor production of industrially important biomolecules and provides key considerations to use CRISPR/Cas systems in microalgae. The review will help researchers to understand the progress and to initiate genome editing experiments in microalgae.